Pelatihan Dasar Jaringan Komputer Untuk Siswa SMK Garuda Nusantara - Arwan Sulaeman, Asep; Fauziah, Sifa; Triwibowo, Edi; Soejarminto, Yos (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2024)
Basic Computer Networking Training for Garuda Nusantara Vocational High School students was held as an effort to improve students' basic competencies in Information and Communication Technology, particularly in computer networking. This activity aims to provide theoretical and practical understanding of basic networking concepts, network hardware, basic configuration, and practical application of local area networks (LANs). The training methods used were interactive lectures, live demonstrations, and field practice, enabling students to understand and apply the material directly. The training results demonstrated an increase in students' knowledge and skills in network installation, IP address recognition, and simple network connection management. This training is expected to be a first step for students in preparing themselves for the world of work in the field of computer networking technology. Keywords: training, computer networking, vocational high school students, information technology, basic skills.